Sociodemographic disparities in influenza vaccination among older adults in United States - Tao, Huan; Chen, Jin; Zhang, Xue; Wang, Tao; Jiang, Nenggang; Jia, Yongqian (Frontiers in Public Health, 2025)
BackgroundInfluenza vaccination uptake among United States adults aged 65 years or older remains suboptimal and stagnant. This study aims to evaluate the prevalence of influenza vaccination and examine sociodemographic disparities within a nationally representative sample.MethodsThis study is a cross-sectional study. We used the data from the Behavioral Risk Factor Surveillance System spanning the years 2011 to 2022. Logistic regression models were used to assess potential associations between influenza vaccination uptake and sociodemographic characteristics. Concentration indexes were also calculated to measure the socioeconomic inequalities on influenza vaccination uptake.ResultsThe study included 1,391,440 adults aged 65 years and older, with 62.87% reporting having received an influenza vaccination. The weighted prevalence of influenza vaccination uptake showed a slight increase, ranging from 59.05% in 2011–2013 to 67.49% in 2020–2022. Higher vaccination rates were observed among non-Hispanic Whites [63.16%; odds ratio (OR) 1.38, (95% CI 1.33–1.42)], individuals with education above high school [63.89%; OR 1.16, (95% CI 1.12–1.19)], and those with an income above $50,000 [65.86%; OR 1.47, (95% CI 1.43–1.50)]. Compared to non-Hispanic Black people with an income below $25,000 and education less than high school, the ORs were significantly higher among non-Hispanic whites [2.12, (95% CI 1.97–2.28)], non-Hispanic Black people [1.30, (95% CI 1.18–1.44)], and Hispanics [1.40, (95% CI 1.24–1.59)] earning above $50,000 and education above high school. Those who received an influenza vaccination tended to be concentrated in the high-income group and high-education group.ConclusionThere are substantial racial and socioeconomic disparities in influenza vaccination uptake among individuals aged 65 years or older. Health policy maybe urgently needed to reduce these avoidable inequalities.